Gouvernements Burgerlijke Zienkenrichting Te Pandeglang 1914-1925 - Moch Alfath Nurussalam; Usmaedi Usmaedi (Program Studi Pendidikan Sejarah, Universitas Setiabudhi Rangkasbitung, 2026)
This research aims to examine the history, architecture, social dynamics, and changes in function of the former Pandeglang Regional General Hospital (RSUD) building, which now functions as a Regional Library. This building holds significant historical value as the first hospital in Pandeglang Regency, established during the Dutch East Indies colonial period, around 1914, as part of the implementation of the Ethical Policy policy in the health sector. As a colonial medical institution, this hospital was not only a center of healing, but also played a role as an instrument of power in social control and public health. In the social context, the establishment of the hospital faced cultural resistance due to local people's belief in traditional medicine, which slowly changed along with the hospital's success in handling the Frambousia Tropica outbreak in the 1920s. This study uses historical research methods with archival document analysis, as well as interviews with local history academics, to reconstruct a complete and factual narrative. With methods such as Heuristics, source criticism, interpretation and historiography. The research findings confirm that the former Pandeglang Regional General Hospital is a historical heritage that deserves to be preserved, not only as a cultural heritage building, but also as a symbol of the evolution of the health system and changes in people's mindsets. From the results of the study, it was found that in terms of architectural aspects, this building reflects a colonial style with typical elements such as porticoes, jalousie windows, dormer windows, and the use of teak wood materials, which not only function aesthetically but are also adaptive to the tropical climate. From the discussion, the following conclusions can be drawn: This research reveals that the Gouvernements Burgerlijke zienkenrichting, or former Pandeglang Regional Hospital building, holds significant historical, architectural, and social significance in the development of the health system and culture of the Pandeglang community. Originally a civil hospital, this building was built during the Dutch colonial period as part of the implementation of the Ethical Policy in the health sector. The hospital's establishment not only aimed to improve public health but also served as a means of social control and part of the colonial infrastructure that began in 1914. Keywords: Gouvernements Burgerlijke zienkenrichting; former Pandeglang Regional Hospital building; Frambousia Tropica; Dutch Colonial